2014
DOI: 10.7860/jcdr/2014/8295.4510
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Two Different Dosages of Intrathecal Magnesium Sulphate Supplementation in Subarachnoid Block

Abstract: INTRODUCTIONRegional anaesthesia is a safe, inexpensive technique, widely used for lower limb orthopaedic surgery due to the advantage of prolonged post-operative pain relief. Combination with adjuncts [1][2][3][4][5] like epinephrine, clonidine, neostigmine, opioids, midazolam and magnesium [6][7][8][9][10][11][12][13][14][15][16][17][18][19] have been used to prolong analgesia and reduce the incidence of adverse events. These spinal adjuvants allow the use of lower dose of local anaesthetic agents, prolong a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Several previous studies [13, 19, 21, 22] reported that the duration of spinal anesthesia was significantly prolonged by intrathecal magnesium sulfate, which is consistent with the findings in the present study. The present study also showed that adding magnesium sulfate intrathecally could significantly prolong the duration of spinal anesthesia with bupivacaine and sufentanil (184 min vs 148 min, P  < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Several previous studies [13, 19, 21, 22] reported that the duration of spinal anesthesia was significantly prolonged by intrathecal magnesium sulfate, which is consistent with the findings in the present study. The present study also showed that adding magnesium sulfate intrathecally could significantly prolong the duration of spinal anesthesia with bupivacaine and sufentanil (184 min vs 148 min, P  < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…The ED 50 of intrathecal hyperbaric bupivacaine for cesarean delivery, determined using Dixon and Massay up-down sequential method [19, 20], was 4.7 mg (95% CI, 4.4–5.0 mg) in the Control group, and 4.9 mg (95% CI, 4.6–5.2 mg) in the Magnesium group. There was no significant difference in the ED 50 of bupivacaine between the Magnesium group and the Control group ( P  = 0.53).…”
Section: Resultsmentioning
confidence: 99%
“…There was no nausea in magnesium sulphate group as reported in other studies. 17,18,23 This finding suggests t hat magnesium sulphate probably has inhibitory action on nausea which may be advantageous compared to intrathecal opioids .…”
Section: Discussionmentioning
confidence: 92%
“…Similar findings were observed in other studies. 17,[21][22][23] Among these studies, two studies 17,23 compared magnesium sulphate as adjuvant to intrathecal bupivacaine where as in the other two studies 21,22 intrathecal fentanyl was also added and concluded the same. The duration of motor block was same in both the groups in another study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Intrathecal magnesium has shown promising results by prolonging the duration of analgesia in various surgical procedures like lower limb surgeries. 8,9 The aim of study was to compare the effects of intrathecal dexmedetomidine and magnesium sulphate as adjuvants to bupivacaine for lower abdominal and lower limb surgeries in relation to characteristics of sensory block, motor block and sedative effect.…”
Section: Introductionmentioning
confidence: 99%